Ontogenes in Drosophila Melanogaster and a Model of Speciation - B.F. Chadov; N.B. Fedorova (Journal of Evolutionary Science, 2024)
A new type of mutations-dominant lethals with a facultative manifestation -were discovered in D. melanogaster in 2000. These mutations were named conditional mutations. Under restrictive genetic conditions, the mutations manifest themselves as dominant lethals, whereas dominant lethality disappears under permissive conditions, displaying a set of other manifestations. The genes responsible for the emergence of conditional mutations were named ontogenes. The experiments with mutations in ontogenes have revealed the following processes: (1) genome editing in germline cells; (2) induction of high mutagenesis rates in germline cells of the mutants for ontogenes; (3) zygotic selection; (4) isolation of mutants; and (5) alterations in the lethality of mutants with time. The specific features in the manifestation of ontogenes together with the listed processes formed the background for construction of the model of speciation named the regeneration model. The event of speciation is represented as the regeneration of the working state of a genetic system disturbed by the emergence of a mutation in an ontogene. According to the model, it is ontogenes that are in charge of speciation and, eventually, the structure of living matter in the form of individual species. The significance of Mendelian protein-coding genes and Darwinian selection of the fittest according to these genes are doubtless but not paramount.
Keywords: Darwinian selection